PHENOMENON OF DEMIKHOV. The origin of the assisted circulation concept and its implementation (V.P. Demikhov, 1937–1947) - S. P. Glyantsev; A. Werner (Трансплантология (Москва), 2022)
It is generally accepted that the concept of mechanical circulatory support originates from the USA in the 1960s and was implemented in the clinic by American surgeons S. Crawford, M. DeBakey, D. Cooley, D. Liotta and others by creating portable implantable pneumatic devices included in the cardiovascular system parallel to the biological heart to maintain its activity in heart failure. However, we found that twenty years earlier, in 1947, a similar concept was first put forward by the Soviet biologist and physiologist V.P. Demikhov, who had implemented it in an experiment by creating implantable electromechanical devices and transplanting a second, additional heart into the animal chest. At the same time, V.P. Demikhov suggested using his models both for maintaining the function of a weakened biological heart and for its recovery. Since an idea similar to that published in an English-language edition had never been formulated by anyone before V.P. Demikhov, his priority is global.